The Evolution of MALDI-TOF Mass Spectrometry toward Ultra-High-Throughput Screening: 1536-Well Format and Beyond - Haslam, Carl; Hellicar, John; Dunn, Adrian; Fuetterer, Arne; Hardy, Neil; Marshall, Peter; Paape, Rainer; Pemberton, Michelle; Resemannand, Anja; Leveridge, Melanie (Journal of biomolecular screening, 2016)
Mass spectrometry (MS) offers a label-free, direct-detection method, in contrast to fluorescent or colorimetric methodologies. Over recent years, solid-phase extraction-based techniques, such as the Agilent RapidFire system, have emerged that are capable of analyzing samples in <10 s. While dramatically faster than liquid chromatography-coupled MS, an analysis time of 8-10 s is still considered relatively slow for full-diversity high-throughput screening (HTS). Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF) offers an alternative for high-throughput MS detection. However, sample preparation and deposition onto the MALDI target, as well as interference from matrix ions, have been considered limitations for the use of MALDI for screening assays. Here we describe the development and validation of assays for both small-molecule and peptide analytes using MALDI-TOF coupled with nanoliter liquid handling. Using the JMJD2c histone demethylase and acetylcholinesterase as model systems, we have generated robust data in a 1536 format and also increased sample deposition to 6144 samples per target. Using these methods, we demonstrate that this technology can deliver fast sample analysis time with low sample volume, and data comparable to that of current RapidFire assays.